On the road to per cent accuracy VI: the non-linear power spectrum for interacting dark energy with baryonic feedback and massive neutrinos. Issue 3 (10th March 2022) - Carrilho, Pedro; Carrion, Karim; Bose, Benjamin; Pourtsidou, Alkistis; Hidalgo, Juan Carlos; Lombriser, Lucas; Baldi, Marco
ABSTRACT: Understanding non-linear structure formation is crucial for fully exploring the data generated by stage IV surveys, requiring accurate modelling of the power spectrum. This is challenging for deviations from Λ cold dark matter, but we must ensure that alternatives are well tested, to avoid false detections. We present an extension of the halo model reaction framework for interacting dark energy. We modify the halo model including the additional force present in the Dark Scattering model and implement it into ReACT . The reaction is combined with a pseudo-spectrum from EuclidEmulator2 and compared to N -body simulations. Using standard mass function and concentration-mass relation, we find predictions to be 1 per cent accurate at z  = 0 up to k  = 0.8  h  Mpc −1 for the largest interaction strength tested (ξ = 50 b GeV −1 ), improving to 2  h  Mpc −1 at z  = 1. For smaller interaction strength (10 b GeV −1 ), we find 1 per cent agreement at z  = 1 up to scales above 3.5  h  Mpc −1, being close to 1  h  Mpc −1 at z  = 0. Finally, we improve our predictions with the inclusion of baryonic feedback and massive neutrinos and study degeneracies between the effects of these contributions and those of the interaction. Limiting the scales to where our modelling is 1 per cent accurate, we find a degeneracy between the interaction and feedback, but not with massive neutrinos. We expect the degeneracy with feedback to be resolvable by including smaller scales. This work represents the first analytical tool for calculating the non-linear spectrum for interacting dark energy models.